Human Rights without Objective Intrinsic Value - Cantero-Flores, Víctor; Parra-Dorantes, Roberto (Labyrinth, 2019)
The current predominant conception of human rights implies that human beings have objective intrinsic value. In this paper, we defend that there is no satisfactory justification of this claim. In spite of the great variety of theories aimed at explaining objective intrinsic value, all of them share one common problematic feature: they pass from a non-evaluative proposition to an evaluative proposition by asserting that a certain entity has intrinsic value in virtue of having certain non-evaluative features. This is a step that cannot be justified. In light of this negative result, we offer a radically different approach to intrinsic value. Our proposal reinterprets the claim that human beings have intrinsic value in terms of a commitment to value human beings intrinsically. This commitment provides both objective practical reasons for, and a rational explanation of, efforts aimed at defending and promoting human rights, without need to appeal to the existence of objective intrinsic value.